Determinants of CO2 emissions in the BRICS economies: The role of partnerships investment in energy and economic complexity. (June 2022) - Caglar, Abdullah Emre; Zafar, Muhammad Wasif; Bekun, Festus Victor; Mert, Mehmet
Graphical abstract: Abstract: The anthropogenic implications of energy consumption, real income level, and natural resources abundance have been well documented in the environmental economics literature. However, given the uniqueness of many economies i.e., partnerships investment in energy and economic complexity around the globe, it is imperative to investigate the nexus between the outlined variables in a carbon-income framework. To this end, we leverage on second- generational panel methods for its superiority over first-generation model over annual frequency data from 1990 to 2018 for the case of BRICS countries. Empirical findings show that positive changes in trade openness and economic complexity stimulate environmental quality. On the contrary, economic growth, natural resources and public-private partnership contribute to environmental degradation. Based on these results, new insights are obtained for the policymakers, and policies are recommended to develop the environmental quality in BRICS economies.